Dar dėl Kárvaičių vardo kilmės - Ambrazas, Saulius (Baltistica, 2010)
ONCE MORE ABOUT ORIGIN OF THE NAME Kárvaičiai In the present paper the origin of the old village name Kárvaičai in Kuršių nerija (Kurische Nehrung) is discussed. It might has been based on the Baltic colour term *karvas (cf. Lith. karvus ‘bald’, Latv. karva ‘black soil; peat’), which, on one hand, is supposed to be the variant of Lith. šárvas, šìrvas/šir̃vas ‘gray’ (by postulating an interchange of consonants *k : *k’), on the other hand, it can be compared with Lith. kéršas ‘piebald, dapple’, OPruss. kirsnan (swarcz) E 460, Slav. *čьrnъ, OInd. kr̥ṣṇá- ‘black’, and side by side with Lith. karvẽlis ‘pigeon’ (it was already widespread in the 16th century) belonged to the derivational category of nomina attributiva, and had the primary meaning ‘which is bald, gray’, cf. also Lithuanian hydronyms Kar̃vė, Kar̃vis, Karvỹs, Karvedà (a part of them covers the territory inhabited by the Curronians).